2015
DOI: 10.4236/aid.2015.54022
|View full text |Cite
|
Sign up to set email alerts
|

Status of ESBL Producing Bacteria Isolated from Skin Wound at a Tertiary Care Hospital in Bangladesh

Abstract: Background: ESBL producing bacteria are increasing with an alarming rate with a wide range of infections. Objective: The purpose of the present study was to see the status of ESBL producing bacteria isolated from skin wounds. Methodology: This cross sectional study was conducted in the Department of Microbiology at Mymensingh Medical College, Bangladesh from January 2011 to June 2011 for a period of 6 months. All the patients, at any age with both sexes presented with skin wound infection, were taken as study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
1
Order By: Relevance
“…Notably, our results for most frequently isolated species, namely, S. aureus 23.7% and CoNS 15.8%, revealed to be different from those of other studies, where Klebsiella species (88.88%) were the most common ESBL producers from the skin wound infections, E. coli (61.5%) and Pseudomonas species (100.0%) (Yasmin et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, our results for most frequently isolated species, namely, S. aureus 23.7% and CoNS 15.8%, revealed to be different from those of other studies, where Klebsiella species (88.88%) were the most common ESBL producers from the skin wound infections, E. coli (61.5%) and Pseudomonas species (100.0%) (Yasmin et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…were highly resistant to tetracycline, rifampin, nalidixic acid, and 100% sensitive to imipenem. Yasmin et al (2015) [45] also found that Klebsiella isolates were amoxicillin and nalidixic acid resistant [46]. In contrast, we found the isolates of our study were mostly imipenem, meropenem and amikacin sensitive.…”
Section: Discussionsupporting
confidence: 39%